(untitled) (PYC Nepal Journal of Management, 2011)
This study examines the influence of job related variables of blue-collar workers on their desire to participate in managerial decisionmaking process by using survey data. Among the eighty-one percent of workers who showed strong desire to participate in managerial decisionmaking process, found significantly different across their years of experience, level of job satisfaction, and nature of employment. The results show that the workers with long years of experience and permanent nature of job showed high desire to participate in decision-making as compared to their counterparts in the respective groups. However, the workers with high level of job satisfaction preferred less to participate in the management decision-making process. Therefore, management is suggested to practice the scheme by considering the influence of job variables in order to get the support of workers for the betterment of organization and minimize the industrial problems. Since workers involvement in managerial decision-making process not only enhances the benefit to the workers and labor productivity but also creates a sense of satisfaction and security among the workers increasing their efficiency.